Vertical jumps performance analysis: Implementation of novel complex of jumps - Zakharova, A.; Mekhdieva, K. (Proceedings of the 8th International Conference on Sport Sciences Research and Technology Support, 2020)
The proposed study was focused on justification of complex of vertical jumping tests analysis for practical applications of athletes` enhancement. Eighteen national level female athletes aged from 18 to 25 (13 basketball-players and 5 biathletes) underwent anthropometric measurements and set of vertical jumping tests on the force plate. To obtain comprehensive data on jumps performance and motor assymetry classic countermovement and squat jumps were supplemented by countermovent jump with arms swinging and single-leg jumps (on the right and left leg separately). Descriptive and comparative analysis were applied for further statistical data processing. We found that: (i) mean values of body composition variables were within the norm in both groups, meanwhile, biathletes had significantly higher relative body and leg muscle mass; (ii) there were no significant differences in countermovement jump performance between basketball players and biathletes except longer duration of squat and ta ke-off phases in biathletes; (iii) squat jump performance analysis revealed significantly higher strength of knee extensors in female biathletes; (iv) jump height in countermovement jump with arms swinging was significantly higher in biathletes` group; (v) motor asymmetry of lower extremities was more evident in basketball players. The proposed set of different vertical jumps provides with valuable information on fitness level in athletes.